2014
DOI: 10.1080/19325037.2013.853001
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Peer Helper Component of Go !: A Multimessage, Multi-“step” Obesity Prevention Intervention

Abstract: Background: Obesity prevention efforts typically involve changing eating and exercise behaviors as well as the physical and social environment in which those behaviors occur. Due to existing social networks, worksites are a logical choice for implementing such interventions. Purpose: This article describes the development and implementation of a peer helper intervention, which was part of a multicomponent obesity prevention program conducted at a hospital worksite. It also presents qualitative evaluation findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Focus groups with PPACs revealed they were aware that behaviour change is a sensitive subject and tried to tread a fine line between providing support and encouragement for PA, yet not being perceived as critical of individuals who did not engage in planned PA. This awareness is consistent with previous findings in relation to workplace diet and PA interventions (21,22). Both these studies found that champions tended to wait for their peers to approach them with questions about health, or made opportunistic use of conversations that arose spontaneously in the workplace.…”
Section: Theme 2: Valuable Characteristics Of Ppacssupporting
confidence: 81%
See 1 more Smart Citation
“…Focus groups with PPACs revealed they were aware that behaviour change is a sensitive subject and tried to tread a fine line between providing support and encouragement for PA, yet not being perceived as critical of individuals who did not engage in planned PA. This awareness is consistent with previous findings in relation to workplace diet and PA interventions (21,22). Both these studies found that champions tended to wait for their peers to approach them with questions about health, or made opportunistic use of conversations that arose spontaneously in the workplace.…”
Section: Theme 2: Valuable Characteristics Of Ppacssupporting
confidence: 81%
“…Capturing this information is important in order to identify the key ways in which champions positively influence colleagues' health behaviour and so in turn to enhance workplace health champion recruitment and training. To our knowledge only three such studies have been published to date (21)(22)(23). A literature search identified no qualitative studies which evaluated workplace champions who focussed solely on promoting PA.…”
Section: Health Champions In the Workplacementioning
confidence: 99%
“…The most frequently mentioned links to sustainability of interventions or intended outcomes were human and financial resources . Where interventions were able to mobilize existing resources, authors reported enhanced community ownership and sustainability .…”
Section: Resourcing – Financial Human Resources and Othermentioning
confidence: 99%
“…It is difficult to assess the degree of fidelity with which the influentials acted upon their prescribed role, as they were not assessed during the study on their acquisition of knowledge or skills on which they were trained. However, qualitative data from interviews with a subset of 20 influentials suggest that the role of a “peer helper” was embraced by most participants [ 38 ]. These influentials reported modeling recommended behaviors and having more conversations with their coworkers about healthy eating and physical activity; although they were more comfortable with some topics (e.g., “Let’s take the stairs.”) than with others (e.g., “Let’s not buy that ‘red’ food.”).…”
Section: Resultsmentioning
confidence: 99%
“…Such broader changes were seen after the conclusion of the study period. Further details of the selection procedures, trainings, and assessment related to this component were published elsewhere [ 38 ].…”
Section: Methodsmentioning
confidence: 99%